Rethinking Irish History - O'Mahony, Patrick. author. aut Link
VI, 222 p.
Keywords: This book provides a critical interpretation of the construction of Irish national identity in the longer perspective of history. Drawing on recent sociological theory, the authors demonstrate how national identity was invented and codified by a nationalist intelligentsia in the late nineteenth century. The trajectory of this national identity is traced as a process of crisis and contradiction. One of the central arguments is that the negative implications of Irish national identity have never been fully explored by social science.